The Part-Time Wage Penalty : A Career Perspective - Giovanni Russo; Wolter H.J. Hassink (Institute for the Study of Labor (IZA), 2005)
Part-time employment has become an extremely popular work arrangement in the Netherlands because it renders employment compatible with non-work activities. We posit that there may be a downside to part-time employment, which is related to its negative effects on workers? career. This may be the case when firms use promotions to stimulate skill acquisition and human capital accumulation or when they base their work incentive schemes on performance measures that are affected by the number of hours worked or when they screen workers on the basis of the number of hours worked. Because promotions are an important source of wage growth, the low incidence of promotion among part-time workers may contribute to the emergence of the part-time wage penalty (i.e., the wage difference between a part-time worker and an otherwise equal full-time worker) in due time. Consistent with this view, we find that (male and female) workers in part-time jobs are characterized by a lower incidence of promotion relative to workers in full-time jobs and that promotions account for a wage growth of eight log points. Moreover, we find that the part-time wage penalty does not arise at the onset of a career as young workers join the labor market but that it tends to develop over time as labor market experience and the effect of missed promotions cumulate.
Keywords: J24; J31; J22; 330; wages; wage gap; part-time employment; promotions; Teilzeitarbeit; Erwerbsverlauf; Lohnstruktur; Schätzung; Niederlande